PENGARUH CURRENT RATIO (CR), RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), DAN SIZE TERHADAP HARGA SAHAM - Dewi Astutik, 12.05.51.0002; ., Sri Sudarsi (Students Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of current ratio, Return On E quity, Debt to Equity Ratio, and size to the stock price. The research was conducted on a manufacturing company have listed on the Indonesian Stock Exchange periodic 2011-2013. The sampling method in this study using purposive sampling method. The data used in this research is data from manufacturing companies that meet the selection criteria . The analytical method used in this studyis multiple regression analysis. The multiple regression shows thatCR, ROE and Size have positive and significant impact on stock prices, while DER has positive and not significant on stock prices. Adjusted R Square is 0,689 this means 68,9% of the dependent variable can be explained by the independent variable, while the remaining 31,1% is explained by other causes outside the model Keywords: Stock Price, Return On Equity, Debt to Equity Ratio and Size